Development Effect of Teacher Professional Abilities Through Training on The Professional Competency of Teachers And Teacher Performance of State Junior High Schools in the City of Bandung - Dadang Rahman Munandar; N Fathurrohman (International Journal of Nusantara Islam, 2020)
The development of teacher professional abilities through training is an effort to improve teacher performance by increasing their professional competence. The main objective of developing teacher professional abilities through training is to solve teacher performance weaknesses both at present and in the future towards a more desirable level of performance. Because the development of teacher professional abilities through training is so important and requires a lot of money, it is necessary to research to find a real effect on teacher competence and performance. The research problems formulated are: 1) dimensions of teacher professional ability development through training; 2) teacher professional competence; and 3) teacher performance. The research approach is quantitative with a sample of 335 from a population of 2,064 junior high school teachers in Bandung. Data were obtained from teachers using a questionnaire. The data is processed and interpreted using path analysis as an inferential statistical technique by first testing statistical assumptions, including transforming ordinal data into intervals and data normality testing. The study concluded that the development of teacher professional abilities can improve teacher competence and performance, which is expected to ultimately improve the quality of student learning. The implications include: 1) it is necessary to develop effective training; and 2) competence with performance is important to promote better teaching and learning. Based on these implications, there are several recommendations, namely: 1) increasing the development of teacher professional abilities through technical assistance and quality control group forums; (2) designing the development of teacher professional abilities that have a direct impact on the teaching and learning process; (3) develop a model with competency as the dependent variable; and (4) recommend the human side of the organization as a determinant factor that needs to be investigated.